Evaluation of a Conceptual Model of the Relationships of Communication Patterns and Love Styles with Marital Burnout: The Mediating Roles of Forgiveness and Self-Worth among Married Women - Charsetad, Hossein; Moharami, Jafar; Jafari Kadijani, Nasrin (KMAN Counseling & Psychology Nexus, 2027)
The present study aimed to evaluate the fit of a conceptual model explaining the relationships of communication patterns and love styles with marital burnout, considering the mediating roles of forgiveness and self-worth among married women. The research employed a descriptive design based on correlational modeling. The statistical population consisted of all married women residing in Tehran. The sample size was determined using the formula N ≥ 50 + 8M, recommended by Tabachnick and Fidell, as well as Cochran’s formula. Accordingly, 385 married women were included in the analysis. Participants were selected through convenience sampling from five geographical areas of Tehran: north, south, east, west, and central Tehran. The data collection instruments included a demographic information form assessing age, occupation, educational attainment, and duration of marriage; the Pines Couple Burnout Measure (1996); the Communication Patterns Questionnaire developed by Christensen and Shenk (1991); Sternberg’s Triangular Love Scale (1986); the Family Forgiveness Scale developed by Pollard, Anderson, and Jennings (1998); and the Contingencies of Self-Worth Scale developed by Crocker et al. (2003). Following data collection, the data were analyzed using descriptive and inferential statistical methods. Minimum and maximum scores, means, and standard deviations were calculated in the descriptive statistics section. Pearson’s correlation analysis was used in the inferential statistics section, and structural equation modeling was conducted to assess the fit of the conceptual model. Data analyses were performed using SPSS version 25 and AMOS version 26. The hypothesized research model demonstrated an acceptable fit. Communication patterns had a significant negative effect on marital burnout, and love styles had a significant negative effect on marital burnout. Communication patterns had significant positive effects on forgiveness and self-worth, while love styles had significant positive effects on self-worth and forgiveness among married women. Furthermore, communication patterns influenced marital burnout through the joint mediating roles of forgiveness and self-worth, and love styles influenced marital burnout through these two mediators. Communication patterns also influenced marital burnout through forgiveness alone, and love styles influenced marital burnout through forgiveness alone. In addition, communication patterns influenced marital burnout through self-worth, and love styles influenced marital burnout through self-worth among married women.